The global, regional, and national brain and central nervous system cancer burden and trends from 1990 to 2021: an analysis based on the Global Burden of Disease Study 2021 - Zhao, Xueling; He, Menghao; Yang, Renyi; Geng, Nuojin; Zhu, Xinhua; Tang, Ning (Frontiers in Neurology, 2025)
BackgroundBrain and central nervous system (CNS) cancers remain a significant contributor to mortality worldwide. This study aims to provide the latest assessment of the prevalence, incidence, mortality, and disability-adjusted life years (DALY) rates of brain and CNS cancers from 1990 to 2021 at the global, regional, and national levels, stratified by sex, age, and the Sociodemographic Index (SDI).MethodsData from the Global Burden of Disease (GBD) database were used to analyze the age-standardized prevalence (ASPR), incidence (ASIR), mortality (ASDR), and DALY rates of brain and CNS cancers. Joinpoint regression was employed to calculate the annual percent change (APC), and a log-transformed linear regression model was used to estimate the average annual percent change (EAPC) for trend analysis. The data were stratified by sex, 20 age groups, 21 GBD regions, 204 countries/territories, and five SDI quintiles.ResultsIn 2021, there were an estimated 975,279.16 (95% UI, 857,199.67–1,096,203.50) global cases of brain and CNS cancers. The ASPR was 12.01 (95% UI, 10.54–13.52) per 100,000 population; the ASIR was 4.28 (95% UI, 3.71–4.88) per 100,000; the ASDR was 3.06 (95% UI, 2.62–3.50) per 100,000; and the age-standardized DALY rate was 49.58 (95% UI, 28.22–69.92) per 100,000. By SDI regions, the High SDI region showed the highest ASPR and ASIR, the High-Middle SDI region had the highest ASDR and age-standardized DALY rates, and the Low SDI region reported the lowest rates. Geographically, the High-income Asia Pacific region recorded the highest ASPR, Western Europe the highest ASIR, and Central Europe the highest ASDR and age-standardized DALY rates. Overall, in most regions globally, ASIR, ASDR, and age-standardized DALY rates among males increased with age and exceeded those of females. In high-SDI regions, the burden of brain and CNS cancers was predominantly in older adults, whereas in low-SDI regions, the burden among children was pronounced.ConclusionThe global burden of brain and CNS cancers is highest in High and High-Middle SDI regions, with a particularly severe burden in children in Low SDI regions. A comprehensive understanding of the epidemiology of brain and CNS cancers is crucial for strengthening disease prevention and control efforts worldwide.